Language Learning Strategies Used During Online Learning by English Community Members at Lampung - Royan Arif Al Ikhsan (Budapest International Research and Critics University, 2022)
Reading is a receptive skill that is used to obtain information from any text, whereas language learning strategy refers to the processes that learners take in order to attain their learning objectives. The aim of this research is to reveal what language learning strategy as the most used by EFL Students at English club level in a case of pandemic era language learning strategies for reading activity. This research used quantitative design and it involves 20 subjects of all the members and organization in English club. The questionnaire as the instrument of this research. The findings of the research are as the students end to use cognitive strategy as their language learning strategy in their reading activity also it is followed by two others strategies. The researcher also advices for further researcher to conduct the same research interest with large and deep discussions.